Replication of Functional MRI Detection of Deception - Kozel, F. Andrew (2009)
BACKGROUND: Several studies support the use of fMRI for detecting deception. There have been, however, no reported replications on different scanners or at different locations. In a previous study, deception was accurately detected in at least 90% of the participants in two independent cohorts. This study attempted to replicate those findings using a different scanner and location. METHODS: Healthy participants 18–50 years of age were recruited from the local community. After providing written informed consent, participants were screened to ensure that they were healthy, not taking any medications, and safe to have an MRI. For the testing paradigm, subjects chose one of two objects (ring or watch) to “steal” and placed it in their locker. Participants were then scanned while being visually presented with a series of questions. Functional MRI analysis was performed in the same manner as described in Kozel et al. 2005. A Chi-Squared test was used to test for a significant difference between the results in the previous study and in this replication study. RESULTS: Thirty subjects (20 women, mean age 29.0±6.5 years) were scanned with one subject being noncompliant with the protocol. Twenty-five of twenty-nine (86%) participants were correctly identified when being deceptive. There was no statistical difference between the accuracy rate obtained in this study (25/29) versus the previous study (28/31) (Chi-Squared, χ(2)=0.246, p=0.6197). CONCLUSIONS: Our methodology for detecting deception was successfully replicated at a different site suggesting that this methodology is robust and independent of both scanner and location.